Subjective Freedom of Speech: Why Do Citizens Think They Cannot Speak Freely? - Jan Menzner; Richard Traunmüller (Politische Vierteljahresschrift, 2022)
We provide the first systematic research into the origins of subjective freedom of speech in Germany. Relying on the GLES 2021 Cross-Section Pre-Election Survey, which includes a~newly designed survey item on subjective freedom of speech, we evaluate a~whole range of plausible candidate hypotheses. First, we contribute to cumulative research by testing the explanatory factors in Gibson (1993)—citizens' social class, their political involvement and political preferences, and their personality dispositions—for the German case. Second, we move beyond the state of the art and test three new hypotheses that reflect more recent political developments and arguments in the free speech debate: the role of social media, increasing political and social polarization, and the rise of populism. Importantly, all hypothesis tests reported in this paper have been preregistered prior to data collection. Our results reveal that three explanatory factors are significantly, consistently, and substantively related to subjective free speech in Germany: political preferences, populist attitudes, and identification with the Alternative for Germany party.
Keywords: 320; Freedom of speech; Self-censorship; Cancel culture; Populism; German political culture; Freedom of expression; Meinungsfreiheit; Selbstzensur; Cancel Culture; Populismus; Politische Kultur; Redefreiheit